Pengaruh Kenaikan Tarif PPN, Literasi Pajak, Dan Literasi Keuangan Terhadap Potensi Penerimaan Pajak Pertambahan Nilai (PPN) Pada Kecamatan Ilir Timur 1 Kota Palembang - Ilham, Muhammad; Armin, Kusminaini; Putra, Dimas Pratama (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to examine the effect of VAT Rate Increase, Tax Literacy, and Financial Literacy on Potential Value Added Tax (VAT) Revenue. This study uses primary data by distributing questionnaires to 398 people in the Ilir Timur I district of Palembang city. The data were analyzed using multiple linear regression analysis, assisted by IBM SPSS Statistics 25 software. The results of this study indicate that the increase in VAT rates and tax literacy partially affect the potential for VAT revenue. However, financial literacy partially has no effect on potential VAT revenue. The increase in VAT rates, tax literacy, and financial literacy simultaneously affect the potential for VAT revenue.